Hepatic elastin content is predictive of adverse outcome in advanced fibrotic liver disease - Kendall, Timothy; Dolman, Grace; Duff, Catherine; Paish, Emma C.; Zaitoun, Abed; Irving, William L.; Fallowfield, Jonathan A.; Guha, Indra Neil (Wiley, 2018)
Aims. Needle biopsy remains essential for diagnosis in assessment of liver disease, although there remains associated risk. Examination is largely limited to subjective evaluation and biopsies are not exploited to provide personalised prognostic information. Elastin is a durable component of fibrotic matrix in chronic disease, conferring resistance to remodelling and potentially influencing tissue biomechanics linked to portal hypertension. We hypothesised that elastin content was predictive of clinical outcome and so could be quantified to increase the beneficial information yield from a liver biopsy.